Code Mixing and Code Switching in the Speech Events of Intern Students at the South Sulawesi Provincial Language Center - Halidya, Nur; Srimularahmah, Andi; Idris, Muhammad (Bahasa Indonesia Prima, 2025)
This study focuses on analyzing code mixing and code switching in the speech events of student interns at the South Sulawesi Provincial Language Center. This study aims to describe the forms and types of code mixing and code switching as well as the factors that cause code mixing and code switching. The method used in this study is a descriptive qualitative approach because the object of study appears naturally, namely the speech of student interns. The data collection techniques used were observation, recording, conversation, and note-taking. The data analysis used in this study was to identify the data, classify the data, analyze the data according to the research questions, and group the analyzed data. The results obtained from this study were 21 data points, consisting of 11 mixed code data points and 10 code-switching data points. The mixed code data points consisted of 4 data points in the form of words, 2 data points in the form of phrases, 1 data point in the form of word repetition, and 4 data points in the form of clauses. In terms of the type of code-mixing, there were 9 data in the form of internal code-mixing and 2 data in the form of external code-mixing. Meanwhile, the code-switching data were detailed as 7 data in the form of situational code-switching and 3 data in the form of metaphorical code-switching. In terms of type, there were 9 data in the form of internal code-switching and 1 data in the form of external code-switching.